1983
DOI: 10.1111/j.1532-5415.1983.tb02196.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Placement Outcomes of Geriatric Cohorts Receiving Care in a Geriatric Assessment Unit and on General Medicine Floors

Abstract: To assess whether care in a geriatric assessment unit using a multidisciplinary team approach with rehabilitative emphasis impacted on patient placement outcomes, a historical prospective study was initiated using records of geriatric assessment unit patients admitted during a one-year period (n = 62). A second, diagnostically similar general medicine unit cohort was also sampled (n = 62). Placement outcomes of the two groups were compared. All study patients were 75 years of age or older, stratified by source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 9 publications
2
40
0
1
Order By: Relevance
“…Improvement in physical function and reduced disability in older adults with HF at the time of hospital discharge may be functional biomarkers that could be associated with better outcomes 6,7 . Absence of sustained benefits using GEM, as observed in our study, has also been noted in previously published studies 8,9,28 and remains poorly understood. Although the downward spiral of the frailty syndrome was not attenuated over the long term after inpatient GEM in our study, it may be possible to reinforce inpatient GEM management strategies longitudinally in an effort to maintain functional reserves and adaptive capacity in older adults at high risk for clinical deterioration.…”
Section: Discussionsupporting
confidence: 80%
“…Improvement in physical function and reduced disability in older adults with HF at the time of hospital discharge may be functional biomarkers that could be associated with better outcomes 6,7 . Absence of sustained benefits using GEM, as observed in our study, has also been noted in previously published studies 8,9,28 and remains poorly understood. Although the downward spiral of the frailty syndrome was not attenuated over the long term after inpatient GEM in our study, it may be possible to reinforce inpatient GEM management strategies longitudinally in an effort to maintain functional reserves and adaptive capacity in older adults at high risk for clinical deterioration.…”
Section: Discussionsupporting
confidence: 80%
“…One study whose primary aim was to assess patient placement outcomes found no significant difference in patient location (home vs. nursing home) at discharge or 6 months after admission between the geriatric assessment unit and usual care. 25 Rubenstein and colleagues found that patients assigned to the geriatric evaluation unit had a significant reduction in nursing home admissions at discharge but not at 12 months. 1 Several other studies found no significant difference between the GEM and usual care with regards to nursing home placement.…”
Section: Discussionmentioning
confidence: 97%
“…Applegate et al 1983, Cable & Mayers 1983, Teasdale et al 1983 Davies et al 1984, Victor & Vetter 1985, Waters 1987b, Saltz et al 1988 …”
mentioning
confidence: 97%